Development of a UV spectroscopy method to validate p-coumaric acid and assess the antioxidant activity of a p-coumaric acid gel product - Gajbe, Jitendra; Madgulkar, Ashwini; Shinde, Minakshi (Prospects in Pharmaceutical Sciences, 2025)
Ultraviolet spectroscopy is one of the simple, rapid, cost-effective, and precise instrumental methods. The objective of this study was the development of the UV spectroscopy method for the validation of p-coumaric acid according to the International Council for Harmonization guideline [ICH Q2 (R1)] as reported in this work. Antioxidant activity was performed by the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The UV method had not yet been developed for the above drug; this was the research gap, so validation was studied using ethanol and phosphate buffer (pH 6.8). Method A involved the preparation of the sample and standard solutions in ethanol, whereas method B involved the preparation of the solution in a mixture of phosphate buffer (pH 6.8). Two methods were employed to select unique wavelengths for drug analysis. Method A selected 229 nm, whereas method B selected 284 nm. The drug's linearity for method A and method B was found within the concentration range of 2–10 μg/mL (R2=0.98) and 5–25 μg/mL (R2=0.99), respectively, and the accuracy of both methods was evaluated by computing recovery percentages at 80, 100, and 120 percent. It was found that the recovery percentage using both approaches was between 80 and 90 percent. The lower percentage relative standard deviation (RSD) readings indicated how accurate both approaches were. The precision of the procedure was intended to be repeatable both within and between days. The fact that the % RSD value was less than 2 suggests that both approaches are accurate. With the use of ± wavelength variation, the robustness of both techniques was investigated. The active ingredient p-coumaric acid was included in the aqueous gel of HPMC K100M (hydroxypropyl methylcellulose) and Carbopol 971P polymer and its antioxidant activity was evaluated using the DDPH free radical scavenger test (IC50). The result was found to be 0.833 mg/mL. Conclusion: p-coumaric acid in pharmaceutical dosage form was successfully analyzed by the UV method and demonstrated significantly good antioxidant activity.